Humoral innate immunity and the acute phase response 1 - Mantovani, Alberto (Henry Stewart Talks, 2012)
Sensing pathogens and damaged tissues, Complement system activation and regulation, The classical, lectin, and alternative pathways, The MASP family, Collectins
Updated at 2016/08/31